Mapping antibiotic pollution and tracking drivers of environmental AMR in a North Indian pharmaceutical hub - Panwar, Amishi; Uluseker, Cansu; Negi, Gian Singh; Borsetto, Chiara; Taneja, Neelam; Lambert, Helen (Frontiers in Microbiology, 2025)
IntroductionAntibiotic residues in the environment contribute to the escalating threat of antimicrobial resistance (AMR), posing significant risks to public health and ecological systems. Understanding how antibiotics enter the environment during their lifecycle is crucial for developing effective mitigation strategies. This paper maps antibiotic pollution pathways in Baddi, Himachal Pradesh, highlighting the potential environmental and human health impacts of antimicrobial production, consumption, and disposal.MethodsA mixed-methods approach was used, combining qualitative interviews with stakeholders and community members, and quantitative analysis of sales data. Interviews with manufacturers, healthcare providers, and waste management officials provided insights into practices and perceptions related to antibiotic use and disposal. Sales data of four locally manufactured or packaged antibiotics during the COVID-19 pandemic were analyzed to trace their journey through the supply chain and identify potential points of environmental entry for antibiotic residues.ResultsThe study identified several critical points in the antibiotic supply chain where residues could enter the environment, including manufacturing discharge, disposal practices by consumers, and inadequate waste management systems. The analysis revealed an increase in antibiotic consumption during the COVID-19 pandemic, exacerbating the potential environmental burden. Key areas requiring oversight and management were highlighted, such as the need for better waste treatment facilities and stricter regulatory controls.DiscussionThis research emphasizes the urgent need for a coordinated response at both the state and national levels to enhance environmental monitoring, improve waste management practices, and strengthen regulatory frameworks in India. Addressing these issues is essential to mitigate the growing threat of AMR and protect both environmental and human health. The findings advocate for comprehensive strategies involving multiple stakeholders to ensure sustainable management of antibiotics throughout their lifecycle.